Expert opinion on the long-term use of cladribine tablets for multiple sclerosis: Systematic literature review of real-world evidence - Oreja-Guevara, Celia; Brownlee, Wallace; Celius, Elisabeth G; Centonze, Diego; Giovannoni, Gavin; Hodgkinson, Suzanne; Kleinschnitz, Christoph; Havrdova, Eva Kubala; Magyari, Melinda; Selchen, Daniel; Vermersch, Patrick; Wiendl, Heinz; et al. (Multiple sclerosis and related disorders, 2023)
BACKGROUND: Treatment with cladribine tablets (CladT), an immune reconstitution therapy for relapsing multiple sclerosis (RMS), involves two short courses of treatment in Year 1 and Year 2. Most patients achieve sustained efficacy with CladT, but a small proportion may experience new disease activity (DA). Following completion of the indicated dose, physicians may have questions relating to the long-term management of these patients. Since the EU approval of CladT over 5 years ago, real-world evidence (RWE) is increasing and may provide some insights and guidance for clinical practice. We describe a systematic literature review (SLR) of RWE and provide expert opinions relating to six questions regarding the long-term use of CladT. METHODS: Pertinent clinical questions were developed by a steering committee (SC) of 14 international multiple sclerosis (MS) experts regarding breakthrough DA in Year 1, new DA after 2 years or more of treatment, long-term management of stable patients, and whether additional courses of CladT may be required or safe. An SLR was performed in EMBASE and PubMed using the population, intervention, comparators, outcomes, study design (PICOS) framework to identify relevant studies within the last 15 years. Searches of key congress proceedings for the last 2-3 years were also performed. Following review of the results and RWE, the SC drafted and agreed on expert opinion statements for each question. RESULTS: A total of 35 publications reporting RWE for CladT were included in this review. In the real world, breakthrough DA in Year 1 is of low incidence (1.1-21.9%) but can occur, particularly in patients switching from anti-lymphocyte trafficking agents. In most patients, this DA did not lead to treatment discontinuation. Reported rates of DA after the full therapeutic effect of CladT has been achieved (end of Year 2, 3 or 4) range from 12.0 to 18.7% in the few studies identified. No RWE was identified to support management decisions for stable patients in Year 5 or later. Views among the group were also diverse on this question and voting on expert opinion statements was required. Only two studies reported the administration of additional courses of CladT, but detailed safety outcomes were not provided. CONCLUSIONS: RWE for the long-term use of CladT in the treatment of RMS is increasing, however, gaps in knowledge remain. Where possible, the RWE identified through the SLR informed expert statements, but, where RWE is still lacking, these were based solely on experiences and opinion, providing some guidance on topics and questions that occur in daily clinical practice. More real-world studies with longer-term follow-up periods are needed and highly anticipated.
Keywords: Lymphocytes; Recurrence; znalecký posudek; lidé; Cladribine; Multiple Sclerosis; kladribin; Immunosuppressive Agents; lymfocyty; recidiva; Tablets; roztroušená skleróza; tablety; imunosupresiva; Expert Testimony; Humans